2020
DOI: 10.1016/j.ijplas.2020.102743
|View full text |Cite
|
Sign up to set email alerts
|

The role of dwell hold on the dislocation mechanisms of fatigue in a near alpha titanium alloy

Abstract: The dislocation structures appearing in highly mis-oriented soft/hard grain pairs in near-alpha titanium alloy Ti6242Si were examined with and without the application of load holds (dwell) during fatigue. Dislocation pile-up in a soft grain resulted in internal stresses in an adjacent hard grain which could be relaxed by dislocation multiplication at localized Frank-Read sources, a process assisted by the provision of a relaxation time during a load hold. The rate of this process is suggested to be controlled … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Hence, insofar as Bache and Evans' hypothesis provides some of the mechanistic explanation for dwell fatigue, the present study reinforces this aspect that high pile-up stresses do indeed develop within the hard grain. Our previous analytical calculation predicts that the maximum stress plane would be near basal [≈2.5°to (0002)] under dwell fatigue 28 . In addition, the basal dislocations established within the hard grain may also be crucial for the facet nucleation mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, insofar as Bache and Evans' hypothesis provides some of the mechanistic explanation for dwell fatigue, the present study reinforces this aspect that high pile-up stresses do indeed develop within the hard grain. Our previous analytical calculation predicts that the maximum stress plane would be near basal [≈2.5°to (0002)] under dwell fatigue 28 . In addition, the basal dislocations established within the hard grain may also be crucial for the facet nucleation mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive glide in Ti alloys is responsible for creep 26 and subsequent load shedding at room temperature. We have recently studied the dislocation interactions at soft/hard grain boundaries under both low cycle 27,28 and dwell fatigue 28 . 〈a〉-prism pile-ups in the soft grain were observed to nucleate 〈a〉dislocations in the hard grain.…”
mentioning
confidence: 99%
“…Dislocation density has been an important contributor to FIPs in near-α titanium alloys. 1,3,[20][21][22][23] At a lower length scale, experimental observations using high resolution electron backscatter diffraction (HR-EBSD) 24 and transmission electron microscopy (TEM) 25,26 indicate that the dislocation activation in the soft grain and pileups at the hard-soft grain boundaries lead to the stress accumulation in the neighboring hard grain for near-α titanium alloys. Fatigue resistance is intrinsically linked with dislocation relaxation or accumulation, through cyclic dislocation reversal, 27 slip transfer, 25,27,28 and source activation.…”
Section: Introductionmentioning
confidence: 99%
“…25,29 However, till now, dislocation density alone has not been directly linked to the fatigue crack nucleation in near-α titanium alloys. Enlightened by experimental observations in TEM and associated discrete dislocation work showing a high density mismatch of dislocations at hard-soft grain boundary in near-α titanium alloys, 26,27 a new FIP was recently proposed based on the maximum dislocation density discrepancy among all grain pairs in near-α titanium alloys. 30 In addition to its physical basis, this FIP is well suited for implementation in reduced order and multiscale models to predict fatigue initiation at both microstructure and component scales, [30][31][32][33] as well as in uncertainty quantification associated with fatigue crack nucleation.…”
Section: Introductionmentioning
confidence: 99%
“…spatial dislocation interaction and out-of-plane strain, etc. However, independent experimental observation on IMI834 (Baxter et al, 1996;Prasad et al, 2008;Wang et al, 2006) and other near-alpha HCP titanium alloys (Joseph et al, 2020;Joseph et al, 2018) at the mesoscale using transmission electron microscopy (TEM) has demonstrated the importance of the activities of 〈 〉-prism dislocations and their pile-ups, which may be captured by 2D DD formulations (Tarleton et al, 2015;Zheng et al, 2016a). Hence there are significant insights which may be achieved with 2D approaches, even though some aspects of the 3D deformation may not be captured.…”
Section: Introductionmentioning
confidence: 99%